The Influence of Product Quality, Customer Bonding and Customer Satisfaction on Customer Loyalty: (Case Study on Customers of Vira Hijab Bengkalis) - Dilla Syafiqa; Yunelly Asra (Politeknik Kampar, 2024)
This study aims to analyze the influence of product quality, customer bonding and customer satisfaction on customer loyalty at Vira Hijab Bengkalis. This study uses a quantitative method using a non-probability sampling method with purposive sampling. The sample in this study was 100 respondents, data processing used the IBM SPSS version 26 application with multiple linear regression analysis testing which included validity tests, reliability tests, T-tests, F tests, and the coefficient of determination (R2). The results of this study indicate that: 1) product quality has a positive and significant effect on customer loyalty at Vira Hijab Bengkalis, 2) customer bonding has a positive and significant effect on customer loyalty at Vira Hijab Bengkalis, 3) customer satisfaction has a positive and significant effect on customer loyalty at Vira Hijab Bengkalis, 4) the coefficient of determination (R2) is 0.573. This means that product quality, customer bonding and customer satisfaction effect customer loyalty at Vira Hijab Bengkalis by 57.3% while the remaining 42.7% is influenced by other variables not examined in this study.